Local structure, magnetic and electronic properties of N-doped alpha-Cr2O3 from the first-principles - Stashans, A. (2017)
First-principles calculations based on the density functional theory (DFT) within the generalized gradient approximation (GGA) have been used to study the defective alpha-Cr2O3 crystal. Structural, electronic and magnetic properties have been investigated in the periodic crystalline structure containing one and/ or two N impurities. Local structure of defective region reveals a polarization around the impurity due to the atomic distortions. Presence of the N atom reduces the band-gap width of the material. The dopant might induce a local energy state within the band-gap region for some specific impurity concentrations. Discovered changes upon the magnetic properties imply that chromium oxide might not act as an anti-ferromagnetic substance in the presence of N imperfection